The Effect of Health Education on Increasing Knowledge About Diarrhea Disease in Elementary School Students - Surya Syarifuddin (SEAN Institute, 2023)
Diarrhea is a disease that is still a health problem in Indonesia. Patients with diarrhea experience dehydration due to loss of fluid in the body which can cause loss of consciousness and death. Diarrhea cases are caused by factors such as not washing hands with soap, consuming unhygienic food, inadequate latrines, and lack of availability of clean and healthy water. Objective: to determine the effect of health education on knowledge about diarrhea disease in elementary school students before and after being given health education. Method: This study used Pre-experimental method using one group pretest and posttest design. The research sample was grade VI students as many as 45 elementary school students using Total Sampling. The analysis test uses the Wilcoxon Test to determine the effect of health education on increasing knowledge about diarrhea in elementary school students. Results: the results showed that there was a difference between the level of pretest and posttest with the difference in the average value of knowledge of elementary was 1.74 and the Wilcoxon Test analysis showed pvalue=0.00. Conclusion: There is an effect of health education on increasing knowledge about diarrheal diseases in elementary school students. Suggestion: It is expected that the implementation of this health education can be implemented in other schools or in the home environment so that the expansion of this information can increase the knowledge of school students or the community about diarrheal disease so that morbidity and mortality rates due to cases of diarrhea disease can be prevented